Purification, crystallization and preliminary crystallographic studies of Lys48-linked polyubiquitin chains - Morimoto, Daichi (International Union of Crystallography, 2010)
Post-translational modification of proteins by covalent attachment of ubiquitin regulates diverse cellular events. A Lys48-linked polyubiquitin chain is formed via an isopeptide bond between Lys48 and the C-terminal Gly76 of different ubiquitin molecules. The chain is attached to a lysine residue of a substrate protein, which leads to proteolytic degradation of the protein by the 26S proteasome. In order to reveal the chain-length-dependent higher order structures of polyubiquitin chains, Lys48-linked polyubiquitin chains were synthesized enzymatically on a large scale and the chains were separated according to chain length by cation-exchange column chromatography. Subsequently, crystallization screening was performed using the hanging-drop vapour-diffusion method, from which crystals of tetraubiquitin, hexaubiquitin and octaubiquitin chains were obtained. The crystals of the tetraubiquitin and hexaubiquitin chains diffracted to 1.6 and 1.8 Å resolution, respectively. The tetraubiquitin crystals belonged to space group C222(1), with unit-cell parameters a = 58.795, b = 76.966, c = 135.145 Å. The hexaubiquitin crystals belonged to space group P2(1), with unit-cell parameters a = 51.248, b = 102.668, c = 51.161 Å. Structural analysis by molecular replacement is in progress.